Mold Development for Resin Transfer Molding with Dimension Variationand Deformation Compensation - Dong, Chensong; Lynch, Stuart; Li, J. (Trans Tech Publications Inc, 2010)
A method for achieving better dimensional control for composites based on deformation compensation in mold design is presented in this paper. The process-induced deformation of a general angled part, i.e. spring-in, was studied statistically to account for the processing-related uncertainties. The part geometry was modified based on the results from the statistical analysis for offsetting the deformation. The modified part geometry was used to design the mold for resin transfer molding and the mold was made by the CNC wire electrical discharge machining (WEDM) process. Five sample parts were fabricated using the mold and the spring-in angles were measured. The results show that the process-induced deformation is significantly reduced through deformation compensation. This method presented in this paper provides an approach to minimizing the overall process-induced deformation of resin transfer molded parts.